Outsourcing and Labour Justice in Indonesia: Integrating Contemporary Islamic Legal Principles with the National Regulatory Framework - Arpangi; Gunarto; Nanang Sri Darmadi; Trubus Wahyudi (MILRev: Metro Islamic Law Review, 2025)
This study examines the practice of outsourcing labour in Indonesia by integrating contemporary Islamic legal principles with national labour regulatory frameworks. Using a qualitative approach with field study methods, data were collected through in-depth interviews with outsourced workers, entrepreneurs, labour activists, and Islamic law experts in several industrial areas. The findings indicate that although national laws and regulations, particularly Law Number 13 of 2003 on Manpower and its amendments, formally regulate outsourcing mechanisms, their practical implementation often fails to ensure substantive justice for workers. Many outsourced employees continue to face significant challenges, including job insecurity, unpaid wages, and limited access to social security, which collectively undermine their welfare and dignity. From the perspective of Islamic law, especially when viewed through the framework of maqāṣid al-sharī’ah, the protection of workers’ rights and dignity is an integral objective of the shari‘a, which emphasises justice, public benefit, and the safeguarding of vulnerable groups. This perspective highlights that the ethical and humane treatment of workers is not only a legal responsibility but also a moral imperative grounded in religious principles. By examining the intersection between Islamic legal norms and positive labour law, this study proposes a more ethical and contextual model of employment justice that responds to both regulatory shortcomings and socio-economic realities. The findings contribute to the development of more equitable and sustainable labour policies in Indonesia. Academically, this research enriches the discourse on Islamic law and labour studies by bridging normative theory with empirical realities and offering a framework for future comparative studies on outsourcing practices in Muslim-majority countries.